Optimization of Effervescent Tablets in Sensory Acceptance from the Active Ingredients of Fish Protein Hydrolysate and Microalgae Chlorellae sp. powder - Ita Junita Puspa Dewi; Yuniarti, Tatty; Nanda Anggiani Putri; M.Si, Niken Dharmayanti; Mugi Mulyono; Sri Sugiwati; Pujoyuwono Martosuyono; Aghitia Maulani; Taufik Hidayat (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research 1. FPH and Chlorella sp. microalgae can be used as effervescent tablet ingredients received by panelists. 2. The mixture design method can determine the formula of effervescent tablets made from a combination of FPH and microalgae 3. The best percentage of FPH and microalgae in effervescent tablets was 5.873% and 9.127%.     Abstract Effervescent tablets are a promising delivery system for functional food ingredients, offering convenience and enhanced consumer appeal. This study aimed to optimize effervescent tablet formulations incorporating Fish Protein Hydrolysate (FPH) and Chlorella sp. powder using the d-optimal mixture design method. Thirteen formulations were evaluated for sensory attributes (color, aroma, taste, aftertaste, hedonic scores) and chemical properties (protein, lipid, water content). The optimal formulation, consisting of 5.873% FPH and 9.127% Chlorella sp. powder, significantly improved sensory acceptance (p < 0.05), validated by a robust statistical model (R2 = 0.93). Proximate analysis confirmed the nutritional value, with protein contents of 19.60% and 47.68% in FPH and Chlorella sp., respectively, along with flavonoids (2.69%) in Chlorella sp.. These results demonstrate the successful integration of bioactive compounds into effervescent formulations, addressing consumer demand for sustainable and health-promoting products. This research provides a framework for developing innovative functional food products, contributing to the global advancement of nutraceuticals and sustainable food solutions. Future studies should focus on long-term stability, bioavailability, and consumer acceptability to enhance the commercialization potential of these effervescent tablets.